THE INFLUENCE OF SOCIAL CAPITAL DIMENSIONS ON FARMERS' PRODUCTIVITY IN LAKUKANG VILLAGE, MARE DISTRICT, BONE REGENCY - Nova; Rianti, Marlia; Mahmud, Ernida (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Farmer productivity plays a crucial role in increasing production yields, which directly impacts food security. One factor that can increase farmer productivity is social capital, which assists in production, distribution, and innovation. Higher farmer productivity leads to a stable food supply and more affordable prices, thus creating sustainable economic growth. This study aims to determine the influence of social capital dimensions on farmer productivity in the village of Donggug. The method used in this study is descriptive quantitative with data analysis techniques using multiple linear regression. This study was conducted in Donggug Village, Mare District, Bone Regency, with a population of 177 people and a sample of 35 people. Data collection techniques used a questionnaire. The variables examined in this study consisted of dependent variables (Trust, Participation, Social Norms, and Networks) and independent variables (Farmer Productivity). The results showed that the variables of trust, participation, and social norms did not affect farmer productivity, while networks did. These findings indicate that the existence of networks, especially those related to access to information, markets, and production facilities, plays a significant role in increasing farmer productivity.